Future challenges in measuring Africa's past: Lessons from estimating GDP for the Gold Coast, 1891-1954 - Morten Jerven (African Economic History Network (AEHN), 2012)
There has been a recent surge in research on long term African development. For this research agenda to be fruitful and its theories, it is crucial to have consistent estimates of economic change. This paper contributes with a new GDP time series for Ghana, 1891-1954. The series implies a sustained period of economic expansion from the late 19th century into the 1960s. This suggests a revision of some prevalent truths about the history of economic growth in Sub-Saharan Africa. The paper discusses the potential of creating historical national accounts for other African economies across the colonial and post-colonial period.
Keywords: N17; N27; N37; N47; N57; 330; Afriica; GDP; Gold Coast; Colonialism